2008
DOI: 10.1210/en.2008-0582
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Postnatal Overnutrition Differentially Impact Appetite Regulators and Fuel Metabolism

Abstract: Maternal obesity is increasing, and it is known that the intrauterine experience programs fetal and newborn metabolism. However, the relative contributions of pre- or postnatal factors are unknown. We hypothesized that maternal overnutrition caused by long-term maternal obesity would exert a stronger detrimental impact than postnatal overnutrition on offspring metabolic homeostasis, with additional postnatal overnutrition exaggerating these alterations. Female Sprague Dawley rats were exposed to chow or high-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
216
5
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(256 citation statements)
references
References 42 publications
29
216
5
2
Order By: Relevance
“…Data has predominantly come from studies that use a combined high-sugar/high-fat palatable obesogenic diet. 33,[40][41][42][43][44] Consistently, a hyperphagic phenotype is identified, in particular in male offspring. Although early data suggested that the hyperphagic behaviour was isolated to junk food in preference to chow, 40 more recent data has demonstrated that the overeating phenotype is also observed in chow-fed offspring of obese mothers.…”
Section: Evidence For Excess Energy Intake In the Offspring Of Over-nmentioning
confidence: 74%
“…Data has predominantly come from studies that use a combined high-sugar/high-fat palatable obesogenic diet. 33,[40][41][42][43][44] Consistently, a hyperphagic phenotype is identified, in particular in male offspring. Although early data suggested that the hyperphagic behaviour was isolated to junk food in preference to chow, 40 more recent data has demonstrated that the overeating phenotype is also observed in chow-fed offspring of obese mothers.…”
Section: Evidence For Excess Energy Intake In the Offspring Of Over-nmentioning
confidence: 74%
“…Animal models of alterations to early life feeding clearly show sustained changes in appetite setting and defended weight trajectory. 28,29 Early life may provide a time period for truly effective preventative interventions. 30 Antenatal parental smoking was strongly associated with the above healthy BMI in childhood in this cohort, independent of socioeconomic factors and feeding practices.…”
Section: Discussionmentioning
confidence: 99%
“…9 Possible mechanisms include reduced hypothalamic STAT-3 (signal transducer and activator of transcription 3) phosphorylation 24 or increased levels of the orexigenic neuropeptide Y in offspring, together with reduced levels of POMC (pro-opiomelanocortin). 25 Hence, alterations in the levels of these neuropeptides may affect appetite and sympathetic activation in offspring from mothers fed an HFD and may explain the greater pressor and sympathetic responses to leptin observed in m-HFD rabbits compared with m-NFD rabbits.…”
Section: Hypertensionmentioning
confidence: 99%